Outbreak of Shiga toxin-producing Escherichia coli O104:H4 associated with organic fenugreek sprouts, France, June 2011 - King, Lisa A; Nogareda, Francisco; Weill, François-Xavier; Mariani-Kurkdjian, Patricia; Loukiadis, Estelle; Gault, Gaëlle; Jourdan-DaSilva, Nathalie; Bingen, Edouard; Macé, Muriel; Thevenot, Delphine; Ong, Nathalie; Castor, Christine; et al. (Clinical infectious diseases, 2012)
On 22 June 2011, 8 patients with hemolytic uremic syndrome (HUS) or bloody diarrhea were reported in France. All 8 were attendees of a community center event on 8 June near Bordeaux. Three Escherichia coli cases were confirmed by isolation of Shiga toxin-producing E. coli O104:H4 stx2 aggR producing a cefotaximase (CTX-M) β-lactamase (STEC O104:H4); the same rare serotype caused the outbreak in Germany in May-July 2011. An investigation was initiated to describe the outbreak, identify the vehicle for infection, and guide control measures. We conducted a retrospective cohort study among all adults attending the event, including food handlers. A standardized questionnaire was administered to participants. A case was an attendee who developed HUS or diarrhea between 8 and 24 June. Cases were confirmed by isolation of STEC O104:H4 or O104 serology. Relative risks (RRs) and 95% confidence intervals (CIs) by exposure were calculated using a Poisson regression model. Twenty-four cases were identified (14% attack rate). Of these, 18 (75%) were women, 22 (92%) were adults, 7 (29%) developed HUS, 5 (21%) developed bloody diarrhea, and 12 (50%) developed diarrhea. Ten (42%) cases were confirmed. Fenugreek was the only sprout type with an independent association to illness (RR, 5.1; 95% CI, 2.3-11.1) in multivariable analysis. This investigation identified a point-source STEC O104:H4 outbreak associated with consumption of fenugreek sprouts. Comparison of results from French and German STEC O104:H4 outbreak investigations enabled identification of a common food vehicle, fenugreek sprouts, and resulted in implementation of Europe-wide control measures in July 2011.